Utilization of Instructional Materials in Teaching Chemistry in Senior Secondary Schools in Katsina Metropolis - Lawal, Yazid Rumah; Rumah, Abdulmumin Abdulsalam; Amadi, Jamilu (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study investigated the Utilization of Instructional Materials in Teaching Chemistry in Senior Secondary Schools in Katsina metropolis. The study was conducted with three research objectives, three research questions and three null hypotheses. The study adopted survey research design and used questionnaire and checklist as instrument for data collection. The sample for the study was arrived at using random sampling technique, hence the total of twenty four (24) chemistry teachers and three hundred and seventy (370) students were used as research sample. The analysis of the data collected was done using both descriptive and inferential statistics. Findings among others shows that: there is no significant difference in the availability of instructional materials for teaching chemistry in senior secondary schools in Katsina metropolis as the observed p value 0.310 is greater than the alpha value (p=0.310>0.05), and that there is a significant difference in the utilization of instructional materials in teaching chemistry in senior secondary schools in Katsina metropolis as the observed p value 0.027 is less than the alpha value (p=0.027<0.05). It is recommended that adequate instructional materials for teaching of chemistry in senior secondary schools in Katsina metropolis should be provided by the ministry of education and that teachers should improvise where instructional materials are not available to teach chemistry in the senior secondary schools in Katsina metropolis, among others.